Le yiddish, l'inconscient, les langues - Koenig, et Raphael; Kohn, Max (Literature and Cultural Studies E-Books Online, Collection 2025., 2025)
Si le yiddish est en train de disparaître, « vers où se dirige cette disparition » demandait avec angoisse le poète yiddish Avrom Sutzkever. La question d'une disparition potentielle du yiddish est déclinée dans des œuvres littéraires, des témoignages, et des enquêtes psychanalytiques en une multitude d'autres langues. Les études réunies dans ce volume définissent la confusion linguistique qui en résulte comme un symptôme de ce traumatisme historique, mêlant singulièrement résonances intimes et expériences collectives. Elles illustrent la nécessité de repenser la question des interactions entre les langues, comme un moment essentiel de prise en compte des tragédies historiques et une étape productive vers une compréhension plus nuancée des notions de multiculturalisme et de plurilinguisme, caractéristiques essentielles de notre époque. "Please show me / Where the language will go down", the Yiddish poet Avrom Sutzkever anxiously asked. Questions surrounding the potential disappearance of Yiddish resonate far and wide, in literary works, personal testimonies, social dynamics, and psychoanalytical inquiries in a range of other languages. The studies gathered in this volume all point at the resulting linguistic confusion as a symptom of historical trauma, singularly combining intimate resonances and collective experiences. They also argue for the necessity to sketch out new ways of thinking about interactions among languages as an essential moment of reckoning with historical tragedies and a productive step towards a more nuanced understanding of issues of multi-culturalism and plurilingualism as an essential feature of our times. See Less